Effects of Different Ages of Robinia pseudoacacia Plantations on Soil Physiochemical Properties and Microbial Communities - Luo, Chaoyi; Zhang, Bingxue; Liu, Jiang; Wang, Xiaoxia; Han, Fengpeng; Zhou, Jihai (Sustainability, 2020)
Robinia pseudoacacia is widely planted on the Loess Plateau as a strong drought-tolerant and salt-tolerant species for vegetation restoration. However, this mode of pure plantation has triggered great concern over the soil ecosystem. The aim of this study was to explore the effects of the plantation on soil physiochemical properties, soil microorganisms, and the relationship between them in Robinia pseudoacacia plantations of different ages. Four different ages of Robinia pseudoacacia stands, including 10-year-old, 15-year-old, 25-year-old, and 40-year-old (abbreviated as Y10, Y15, Y25, and Y40, respectively) were selected, and 20 soil physicochemical and biological indicators were determined. The variation in soil microbial biomass was influenced by sampling depth, and consistent with the variations in TN (soil total nitrogen) and SOC (soil organic carbon) during 25 years’ artificial forestation. Soil moisture increased significantly at Y15 and then decreased at Y40 but other soil properties remained relatively stable. The contents of phosphor lipid fatty acid (PLFA) of different microbial groups followed the order of B (Bacteria) > G− (Gram-negative) > G+ (Gram-positive) > A (Actinomycetes) > F (Fungi). The ratios of F/B (Fungi to Bacteria) and Sat/Mono (Saturated PLFAs to Monosaturated PLFAs) of different ages of plantations showed a similar trend, i.e., declined first, then rose, and declined again. The ratios of Cy/Pre (Cyclopropyl PLFAs to Precursor PLFAs) and G+/G− (Gram-positive to Gram-negative) of the soil of all ages of plantations showed a trend of slow growth and a trend of rapid growth, respectively. Redundancy analysis showed that the contents of individual PLFAs and total PLFA were positively correlated with SOC and TN, but variations of soil PLFA ratios mostly depended on other soil properties. After artificial forestation, the ratios of F/B and Sat/Mono were lower than before forestation, while the ratio of Cy/Pre varied with different soil layers. The ratio of G+/G− increased with the increase in afforestation time, peaking at the 25th year. The contents of individual PLFAs and total PLFA may be sensitive indicators of SOC and TN within 25 years’ plantation. Lower ratio of F/B and higher G+/G− suggest that the sustainability of the ecosystem is weaker and the fertility of the soil is lower after plantation of Robinia pseudoacacia.